Linguistic and cultural online communication issues in the global age - St. Amant 1970- (Information Science Reference, 2007)
"This book provides readers with in-depth information on the various linguistic, cultural, technological, legal, and other factors that affect interactions in online exchanges. It provides information that implements effective decisions related to the uses and designs of online media when interacting with individuals from other cultures"--Provided by publisher.